Barriers to a wider Implementation of LMS in Higher Education: a Swedish case study, 2006-2011 - Ramón Garrote Jurado (FernUniversität Hagen, 2013)
This article investigates barriers to a wider utilization of a Learning Management System (LMS). The study aims to identify the reasons why some tools in the LMS are rarely used, in spite of assertions that the learning experience and students' performance can be improved by interaction and collaboration, facilitated by the LMS. Lecturers' perceptions about the use of LMSs over the last four years at the School of Engineering, University of Borås were investigated. Seventeen lecturers who were interviewed in 2006 were interviewed again in 2011. The lecturers' still use the LMS primarily for distribution of documents and course administration. The results indicate that their attitudes have not changed significantly. The apparent reluctance to utilize interactive features in the LMS is analyzed, by looking at the expected impact on the lecturers' work situation.The author argues that the main barrier to a wider utilization of LMS is the lecturers' fear of additional demands on their time. Hence, if educational institutions want a wider utilization of LMS, some kind of incentives for lecturers are needed, in addition to support and training.